- 1-214-256-5804
- info@tutorpace.com

Here each square root number should be simplified further.

√28 = √(2 * 2 * 7). Now pull out the number which is repeating twice inside the radical.

This gives:

And the square root of ‘0’ is 0 ==>

So, √28 + √0 = 2√7+ 0 = 2√7.

Hence the value of the expression √28 + √0 = 2√7.

Here each square root number should be simplified further.

√25= √(5 * 5). Now pull out the number which is repeating twice inside the radical.

This gives:

Now square root of ‘0’ is 0. Therefore we get ==>

So adding the above two answers, we get ==> √25 + √0 = 5 + 0 = 5

Hence the value of the expression √25 + √0 = 5.